Influence of different luminosity levels on the performance of Jundiá larvae (Rhamdia quelen) (Quoy and Gaimard, 1824) (Pisces: pimelodidae) - Behr, Everton Rodolfo (2008)
The objective of the study was to verify the effect of three luminosity levels (T1=1.2 lux; T2=17 lux and T3= 20 lux) on the growing and survival of jundiá larvae (Rhamdia quelen), during 3 rearing weeks in a water-reuse system. During the first experimental week, the larvae were fed with Artemia franciscana nauplii. From the eighth through the twelfth day of the experiment there was a gradual reduction of nauplii feeding. During and after this period, the larvae received ad libitum dry food with 41% of CP and 4,293kcal gross energy/kg. The results showed that the 24-hour dark environment presented better results of standard and total length on the 14th and 21st days, however, without significant differences in the intermediate luminosity level. In relation to weight and product weight versus survival, significant differences between the three treatments were observed, being the best results obtained in T1, followed by T2 and T3 respectively. No significant differences in relation to survival between the treatments were observed. The specific growth rate was of 23.75; 22.82 and 21.90% per day, respectively for T1, T2 and T3 during the 21 days of experiment.